The ivory tower revisited. Issue 2 (3rd March 2016) - Chantler, Abigail
Abstract : The corollary of the concept of the 'ivory tower', as reflected in the writings of Plato and Newman amongst others, was, paradoxically, the vital importance of the university for wider society. Nevertheless from the mid-twentieth century, the esteem in which a 'liberal' university education was held was diminished by rising expectations that higher education institutions would actively contribute to addressing broader socio-economic challenges through 'knowledge-transfer', education for employment, and community service. However while this linear conception of universities' 'third mission' eroded their 'ivory tower' status, the death knell of the 'ivory tower' rings in contemporary literature on higher education, which articulates a dialectical view of its historical development in which the university and wider society are synthesised in the 'engaged university'. With its focus on reciprocal 'knowledge-exchange', the co-creation of knowledge through teaching and learning, and civic engagement, the 'engaged university' embraces the 'other' as intrinsic to its identity. Yet arguably the increasing instrumentalism and democratisation of higher education are irrevocably eroding the academic freedom and institutional autonomy upon which universities' immeasurable contribution to society ultimately depends.